POSTOPERATIVE COGNITIVE DYSFUNCTION: PREDICTORS, DIAGNOSIS, PREVENTION AND TREATMENT - O.N. YAMSHCHIKOV; A.P. MARCHENKO; S.A. EMELYANOV; С.А. IGNATOVA; N.A. MARCHENKO (Avicenna Tajik State Medical University, 2024)
This review describes postoperative cognitive dysfunction (POCD), the incidence of which, according to the results of various studies, ranges from 4% to 65%. The problem of cognitive impairment in the postoperative period has recently received increasing attention from both researchers and practicing physicians of various specialties, especially anesthesiologists-resuscitators who treat these patients at all stages of the treatment process. The prevalence of POCD has yet to be studied in more depth. The relevance of this problem is associated with cognitive deficit, which affects the quality of life of patients, extended duration of inpatient treatment, and increasing frequency of severe life-threatening complications and death. Based on numerous studies, the article presents the main predictors of POCD and describes the main links in the pathogenesis of this condition. Neuropsychological testing is carried out to assess cognitive impairment before surgery and in the postoperative period. It allows for diagnosing this pathology and provides timely prevention and treatment of this condition. If predictors of cognitive dysfunction are identified, correction of the respective disorders is performed. Pharmacological agents are considered as prevention options. Patients with a high probability of POCD are offered neuroprotectors, antihypoxants, antioxidants, neuroplasticity stimulators, and non-steroidal anti-inflammatory drugs (NSAIDs). One of the promising drugs used for the prevention and treatment of POCD and postoperative delirium is dexmedetomidine, an alpha2-adrenergic receptor agonist, a drug with pleiotropic action (anxiolytic, sedative, sympatholytic, and analgesic). Data for this paper on postoperative cognitive disorders were collected from the electronic scientific databases PubMed, Elibrary, Cyberleninka for 2014-2023. This literature review clearly demonstrates the high prevalence of postoperative cognitive impairment, including postoperative delirium. The problem of maintaining and restoring higher mental functions in patients undergoing surgery is one of the global challenges of modern medicine